The Implementation of Flipped Classroom Model in Public Speaking Class during the Emergency Remote Learning - Leni Irianti; Abdurrachman Faridi; Hendi Pratama; Suwandi Suwandi (International Conference on Science, Education, and Technology, 2021)
This research is aimed at describing the implementation of Flipped Classroom Model in Public Speaking class. Recently, the pandemic outbreak pushes the teaching and learning change into emergency remote teaching and learning. Thus, the flipped classroom model is one of the teaching models which offer online teaching process more effective and active. This model is part of the Blended Learning model, which allow the students to learn the materials before the class begin. Therefore, the writers try to implement this teaching model in Public Speaking class. It is expected that by implementing Flipped Classroom Model the teaching and learning process will be more active during pandemic. This research is employed the qualitative research. The participant of this research is the fourth semester students of English Education Department in Universitas Galuh. It assumes that by using flipped classroom model the lecturer will be more prepare in integrating education and technology to support teaching and learning. The writers assume by applying this flipped classroom model the lecturers are easier in giving instruction in asynchronous teaching and learning. This model also offers the students more opportunity in building their critical thinking public speaking class.